Perinatal Outcomes of Small for Gestational Age Neonates Born With an Isolated Single Umbilical Artery - Blum, Maayan; Weintraub, Adi Y.; Baumfeld, Yael; Rotem, Reut; Pariente, Gali (Frontiers in Pediatrics, 2019)
Objective: To investigate pregnancy outcomes of small for gestational age (SGA) neonates born with isolated single umbilical artery (iSUA) compared to SGA neonates without iSUA. Study design: This was a population-based retrospective cohort study. The primary exposure was defined as delivery of a singleton SGA neonate born with iSUA (study group). Delivery of an SGA neonate without iSUA comprised the comparison group. We evaluated adverse perinatal outcomes in all SGA neonates born at the Soroka University Medical Center between the years 1998-2013. Multiple gestations, fetuses with known congenital malformations or chromosomal abnormalities and patients with lack of prenatal care were excluded from the study. Multivariate logistic regression models were constructed to identify independent factors associated with adverse perinatal outcomes. Results: Of 12,915 SGA deliveries, 1.2% (162) were complicated with iSUA. Women in the study group were older with a significantly lower gestational age at delivery compared with the comparison group. Rates of women who conceived after infertility treatments and women with habitual abortions were higher in the study group. Additionally, patients in the study group had significantly higher rates of preterm deliveries (37.7% vs. 12.2% , p<0.001) and amniotic fluid abnormalities (10.5% vs 2.3%, p<0.001 and 13.0% vs 8.4% p=0.04 for polyhydramnios and oligohydramnios, respectively) as compared to the controls. Higher rates of placental abruption (4.3% vs 1.5%, p=0.01), cord prolapse (4.3% vs 0.5%, p<0.001), non-reassuring fetal heart rates (8.6% vs 4.8% p=0.02) and cesarean delivery (36.4% vs 20.3% p<0.001) were noted in the study group. These neonates had a significantly lower birth weight (1988.0±697 vs 2388.3±481 p<0.001) and higher rates of low APGAR scores at the first and fifth minutes after birth compared with controls. Perinatal mortality was also found to be significantly higher among SGA neonates complicated with iSUA (12.3% vs 3.3%, p<0.001). Conclusion: SGA pregnancies complicated with iSUA are at higher risk for adverse pregnancy and perinatal outcomes as compared with SGA pregnancies without iSUA. Key words: Small for gestational age, isolated umbilical artery, perinatal mortality